VARIOUS ACTIVITIES IN TEACHING ENGLISH FOR YOUNG LEARNERS - Dian Mardasari (HOLISTICS, 2020)
Abstract: Teaching English to young learners has become a trend nowadays. In some schools,English has been taught as a local content subject. Teaching young learners is not like teachingadults because children have their own way of learning. Young learners need to feel secure andknow that there are some obvious reasons for learning English. Therefore, teachers have tomotivate them to learn as much as possible in order to be able to communicate fluently usingEnglish. Since children like to play and have fun, the learning and teaching process should besuitable with the characteristics of the children themselves. Various forms of fun activities forchildren are important for their learning and development. This paper will discuss variousactivities in teaching young learners which could enhance their language skills.